IQ, EQ, SQ, and Social Intelligence: Pillars of Moral Strengthening at Batam Integrated Islamic Junior High School - Heri Suprapto (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to analyze the role of intellectual intelligence (IQ), emotional intelligence (EQ), spiritual intelligence (SQ), and social intelligence (SI) in strengthening the morals of students at an integrated Islamic junior high school in Batam City. This study employs a qualitative approach, utilizing a case study method. Data were collected through observation, in-depth interviews, and documentation with teachers, students, and school officials, and then analyzed thematically to find patterns of relationships between variables. The results show that IQ plays a role in shaping students' moral understanding and ethical awareness. EQ supports self-control, empathy, and moral behavior. SQ strengthens religious motivation and consistency in Islamic morals, while SI facilitates the practice of morals in social interactions. These four aspects of intelligence complement each other, forming a solid foundation for strengthening students' Islamic morals. This research confirms that Islamic education, which integrates IQ, EQ, SQ, and SI, can produce students who excel not only academically but also possess noble character. These findings are expected to serve as a reference for Islamic schools in developing a holistic educational model that balances cognitive, emotional, spiritual, and social aspects to produce a generation of Muslims with character and prepared to face the challenges of the times.